Este Lais posemos acá” … Sì, ma dove? - Fabio Barberini (Medievalista)
The paper examines the hypothesis, put forward a few years ago by Pilar Lorenzo Gradín (2013 and 2016), according to which the Lais de Bretanha would have circulated independently and in a different order. A new analysis of the positive data does not confirm this theory. Regardless of the primitive order of the ‘Breton’ cantigas, it is highly probable that the Lais and the associated rubrics were composed at two different times. In particular, the rubrics could be written at the time when the Lais were inserted in the exemplar of the Colocci’s Portuguese Cancioneiros and, consequently, the last sentence of the rubric of B1 (Este lais posemos acá porque era o melhor que foi feito) could justify, not the first position that the text came to assume in the Laissammlung, but the function of “prologue in verse” that the compiler had assigned to B1 in the structure of the collection of cantigas. In addition, the article adds some elements that agree with the hypothesis – already put forward by Carolina Michaëlis de Vasconcellos – according to which D. Pedro, Earl of Barcelos (and his aristocratic circle) was responsible for the insertion of the Lais into the exemplar and the redaction of rubrics.